2009
DOI: 10.1677/joe-09-0056
|View full text |Cite
|
Sign up to set email alerts
|

Shedding light on the intricate puzzle of ghrelin's effects on appetite regulation

Abstract: Ghrelin, a hormone primarily produced by the stomach, has a wide range of metabolic and non-metabolic effects. It also stimulates food intake through activation of various hypothalamic and brain stem neurons. A series of recent studies have explored the intracellular mechanisms of the appetite-inducing effect of ghrelin in the hypothalamus, shedding light on the intricate mechanisms of appetite regulation. AMP-activated protein kinase (AMPK) is a key metabolic enzyme involved in appetite regulation.Calmodulin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 52 publications
1
30
0
2
Order By: Relevance
“…The fatty acid pathways (Lopez et al, 2008) and mitochondrial uncoupling protein 2 (UCP2) (Andrews et al, 2008), have been identified as novel downstream effectors. Combining the recently described data, a pathway by which ghrelin could stimulate appetite has been suggested (Kola & Korbonits, 2009) (Figure 1). …”
Section: Both Havementioning
confidence: 85%
“…The fatty acid pathways (Lopez et al, 2008) and mitochondrial uncoupling protein 2 (UCP2) (Andrews et al, 2008), have been identified as novel downstream effectors. Combining the recently described data, a pathway by which ghrelin could stimulate appetite has been suggested (Kola & Korbonits, 2009) (Figure 1). …”
Section: Both Havementioning
confidence: 85%
“…These results indicate that ghrelin increases the expression and secretion of VEGF 120 and MCP-1, but not through the induction of oxidative or ER stress (Miyokawa-Gorin et al, 2012), on the peripheral adipocytes. Ghrelin decreases AMPK activity in white adipose tissue, while it increases the AMPK activity in the hypothalamus and heart (Andersson et al, 2004;Kola et al, 2005;Kola and Korbonits, 2009;Zhang et al, 2009). Thus, we measured the changes on the ghrelin-stimulated AMPK activity in the adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Orexigenic signals act via adenosine monophosphate-activated protein kinase (AMPK) and increase the dopaminergic transmission from the ventral tegmental area to the nucleus accumbens, enhancing the reward signals. 40 Therefore, the binding of ghrelin to its specific receptor GHSR1a will lead to an increase in intracellular calcium concentration, with consequent activation of CaMKK2 (calmodulin kinase-kinase 2), which will phosphorylate AMPK. 41 In its turn, AMPK will phosphorylate and inhibit acetyl-coenzyme A carboxylase, resulting in decreased levels of malonyl-CoA and subsequent activation of carnitine-palmitoyltransferase-1.…”
Section: Ghrelin -A Peripheral Orexigenic Peptide With Central Actionmentioning
confidence: 99%